Pengembangan Antibodi Poliklonal dari Stadium Oosista, Sporosista, dan Sporozoit Eimeria tenella (THE DEVELOPMENT OF POLYCLONAL ANTOBODY FROM EIMERIA TENELLA OOCYST, SPOROCYST, AND SPOROZOITE STADIUM) - Tresnani, Galuh; Prastowo, Joko; Nurcahyo, Wisnu; Daryono, Budi Setiadi (Jurnal Veteriner; Vol 14 No 2 (2013), 2013)
The research on developing diagnostic method, vaccine, and drugs for coccidiosis has been focused onthe finding of the immunogenic molecule in Eimeria. The identification of this agent will need the antibodywhich can recognize the biomolecule in the antigen. Antibody that has been developed for this purposeshould be analyzed first, and one of the simple methods for analyzing this antibody is through dot blotanalysis. The objective of this research was to analyze the polyclonal antibody which developed from theoocyst, sporocyst, and sporozoite of  E. tenella using dot blot analysis. The antigen for this polyclonalantibody was made from each of the E. tenella stadium by sonication. Fifteen mice, divided into 3 groups,were then injected subcutaneously with each antigen. The sera from these mice were then collected, analyzedby using ELISA and then it will be used for the dot blot analysis. The research result showed that thepolyclonal antibody which has been developed in mice from each antigen can react with the antigen itself.From this result it can be concluded that the developing of this antibody is successful and it can be used forfurther research in immunoproteomic.
Keywords: analisa dot blot, antibodi poliklonal, E. Tenella